The Methods of National Innovation Systems Assessing - Kudryavtseva, Svetlana S.; Shinkevich, Alexey I.; Ostanina, Sofia Sh.; Vodolazhskaya, Ekaterina L.; Chikisheva, Natalia M.; Lushchik, Irina V.; Shirokova, Lidiya V.; Khairullina, Elmira R. (International Review of Management and Marketing, 2016)
The relevance of this problem is reasoned by the fact that the rapid acceleration of changes in the existing economic and institutional environment confronting business entities with new challenges that require new approaches and solutions which in future will also speed up innovation and modernization transformation. The purpose of the article is to develop a comparative assessment of the level of innovative development of the EU countries and Russia with the European innovation scoreboard technique. The leading approach to the study of this problem is the modeling method, allowing the level's evaluation of national innovation systems' innovative development with the help of qualitative and quantitative indicators. This paper proposes a method of matrix ranking of national innovation systems based on integral indices of expenses and benefits of innovation activity. Article submissions are of theoretical and practical significance for the development of models of innovation management, and strategy development of the state innovation policy. Keywords: National Innovation System, Index of Global Competitiveness, Global Innovation Index, Intellectual Capital, Economic Growth. JEL Classifications: C15, F15, H43